The Variability of Values and the Stagnation of the School: from Skylla… to Ithaca - Βρεττός Ιωάννης Ε.; Ρέππα Γλυκερία Π. (Education Sciences, 2021)
The purpose of this article is to provide stimuli for the treatment of justice as a fundamental value of general interest, and self-awareness as a value of more specific importance for us Greeks. Specifically, two examples are offered: on the one hand dilemmas about justice based on Greek culture, and in particular the ancient Greek tradition, and on the other the predominantly Greek deficit, self-knowledge, but also the inability of the Greek school to exploit our cultural heritage. It is a fact that the 'teaching of values' is a matter of the past, which is usually formulated after economic and social crises, but also appears at the dawn of a new century or a new millennium. In the first case, it is most likely due to insecurity, while in the second case, perhaps in the hope of change for the better. In both cases, there is no realized that values ​​are not changing, but the perspective from which we look at them. This means that we must renegotiate the content of the values ​​by trying to remove 'what is not value' rather than defining its exact content, which is impossible. Already Plato himself, dealing with values, resorts to the myth after the deadlocks. In our effort to participate in the discussion of values, we do not examine our own mental and psychic data and are trapped in imported patterns, whether they are models of value teaching or moral development levels.